CRISPR-Cas9 through AAV delivery system as a gene therapy in Parkinson’s disease - Maulana Bagus Adi Cahyono; Ilham Rahmanto; Zahras Azimuth Doman; Galuh Senjani Yulfani Putri; Christopher Surya Lodianto; Pradana Zaky Romadhon (Universitas Muhammadiyah Surabaya, 2023)
The global population living with Parkinson’s disease is estimated to reach 9.4 million people, which has increased significantly since 2016, with a total of 6 million people. Parkinson's is a neurodegenerative disease of the substantia nigra that causes a decrease in dopamine production and is characterized by the appearance of cytoplasmic misfold proteins called Lewy bodies. The study found that abnormalities or mutations in the SNCA and LRRK2 genes correlated with the overproduction of the ɑ-synuclein protein, which forms Lewy bodies that cause Parkinson's. Current Parkinson's medications only temporarily replace lost dopamine but do not treat the direct cause of Parkinson's; this research used qualitative literature study with content analysis, observation, and development; the use of CRISPR-Cas9 through AAV genetic engineering in repairing SNCA and LRRK2 mutant gene. This genetic therapy works by cutting the mutant DNA base sequences in the SNCA and LRRK2 genes and then replacing them with normal sequences through a homology-direct repair mechanism. As a result, the abnormalities or mutations that cause Parkinson's in these two genes can be corrected, so that dopaminergic levels in the brain can return to normal and excessive accumulation of α-synuclein protein can be suppressed.